Roadmap layers and processes: resilient and sustainable care facilities. Issue 9 (4th June 2019) - Pantzartzis, Efthimia; Price, Andrew; Edum Fotwe, Francis
Abstract : Purpose: Health and social care facilities are usually complex buildings that require continuous effort to provide resilient and sustainable responses to changes in demographics, technologies, diseases and models of care. Despite resilience and sustainability concepts being frequently used by practitioners and researchers, ambiguities in their definitions often result in a lack of operational solutions to record, monitor and improve the resilience and sustainability of health and social care facilities. Although the importance and complexity of the issues are widely acknowledged, there is little strategic guidance as to how they should be achieved. The purpose of this paper is to assess the suitability of developing a roadmap for improving the resilience and sustainability of UK health and social care facilities, and to identify the layers and processes needed to construct such a roadmap. Design/methodology/approach: A qualitative approach was adopted, starting with a literature review of different types of roadmaps and their suitability to support the desired improvement objectives. Layers and processes were thus developed using the key issues identified in three recent research streams, and the roadmap was structured. Findings: The major findings have been captured within a three-layer, four-step process generic roadmap for improving the resilience and sustainability of health and social care facilities that can be used to monitor performance, plans future actions and implement response to change. Practical implications: This paper targets decision makers, especially estate managers, but the proposed layers and processes can be modified for other stakeholders. Originality/value: This paper suggests an original approach for the development of a roadmap for resilience and sustainability of health and social care facilities, and specifically of how to structure layers and processes, envisioning a more integrated development of service provision and infrastructure asset management.